Realigning pt krakatau argo logistics business strategy to improve business bottom line - Putra Dwi Kurniawan, Raditya; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2019)
Abstract - PT Krakatau Argo Logistics (PT KAL) is a joint venture multimodal transport service company, affiliated to  PT Krakatau Bandar Samudera and PT Krakatau Steel. Established in 2013, PT KAL is primarily intended to support the supply chain of PT Krakatau Posco through long-term contracts. The year 2015 is a challenging period for PT KAL where world steel price condition decreased causing the evaluation and adjustment of tariff of service significantly reduced from PT Krakatau Posco to PT KAL and  impact to declining in revenue and profit of PT KAL in 2015 to 2017. It is important to obtain strategic business in order to ensure business sustainability. The company must consider external and internal factors that influence future business growth through a series of strategic analysis. A series of strategic analysis such as PESTEL analysis, Porter’s five forces analysis, and competitior analysis are conducted to enable the company to take advantage of external opportunities and minimize the impact of potential threats. The internal analysis using Resource Based View, VRIO, and market industry in logistic busniess. Strategic formulation is conducted refer to the external and internal analysis to propose future appropriate strategy of the company.The implementation of such strategies is done in the short and long term by continuously evaluating to pursue its future 5 years objective of increasing revenue and profitability.Keywords : Logistic Business, Business Strategy, PESTEL analysis, TOWS matrix, Business Model Canvas